The Actin Cytoskeleton at the Immunological Synapse of Dendritic Cells - Rodríguez-Fernández, José Luis; Criado-García, Olga (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cells (DCs) are considered the most potent antigen-presenting cells. DCs control the activation of T cells (TCs) in the lymph nodes. This process involves forming a specialized superstructure at the DC-TC contact zone called the immunological synapse (IS). For the sake of clarity, we call IS(DC) and IS(TC) the DC and TC sides of the IS, respectively. The IS(DC) and IS(TC) seem to organize as multicentric signaling hubs consisting of surface proteins, including adhesion and costimulatory molecules, associated with cytoplasmic components, which comprise cytoskeletal proteins and signaling molecules. Most of the studies on the IS have focused on the IS(TC), and the information on the IS(DC) is still sparse. However, the data available suggest that both IS sides are involved in the control of TC activation. The IS(DC) may govern activities of DCs that confer them the ability to activate the TCs. One key component of the IS(DC) is the actin cytoskeleton. Herein we discuss experimental data that support the concept that actin polarized at the IS(DC) is essential to maintain IS stability necessary to induce TC activation.